Book review D’Agostino et al.: Depth-Bounded Reasoning. Volume I: Classical Propositional Logic: College Publications, 2024, xvii + 225. ISBN 978-1-84890-442-2 (The Reasoner, 2025)
D'Agostino et al. recently launched book on the College Publication series on Logic and Bounded Rationality is reviewed. Applications to human-oriented AI are emphasized.
Keywords: bounded rationality; depth-bounded boolean logics; Book reviews